2014
DOI: 10.1111/j.1532-950x.2014.12219.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tibial Plateau Angle on Cranial Cruciate Ligament Strain: An Ex Vivo Study in the Dog

Abstract: The mechanical testing model used found CCL strain increased with increasing axial load regardless of the TPA. Decreasing TPA decreased strain in the intact CCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…However, current canine models of ACL reconstruction do not closely follow clinical protocol with respect to surgical instrumentation and technique. Intra‐articular grafts have also been associated with high failure rates in canine subjects because of difficulties in controlling load and motion in the early postoperative period in conjunction with the relatively high tibial slope of dogs . Therefore, development and validation of a pre‐clinical, large animal intra‐articular ACL reconstruction model that addresses current limitations is highly desirable.…”
mentioning
confidence: 99%
“…However, current canine models of ACL reconstruction do not closely follow clinical protocol with respect to surgical instrumentation and technique. Intra‐articular grafts have also been associated with high failure rates in canine subjects because of difficulties in controlling load and motion in the early postoperative period in conjunction with the relatively high tibial slope of dogs . Therefore, development and validation of a pre‐clinical, large animal intra‐articular ACL reconstruction model that addresses current limitations is highly desirable.…”
mentioning
confidence: 99%
“…Reducing the TPA had a protective effect on the CCL in dogs with early fiber tearing, as the CCL remained intact in all dogs with stable partial tears (group 1) in the TPLO study and in all but 1 dog in the CBLO study (Figure ). The protective effect results from decreased stress on the CCL after reducing the TPA, as determined by vitro studies and in clinical observations . Preservation of a functional CCL positively affected the appearance of the articular cartilage in group 1 dogs for both studies.…”
Section: Discussionmentioning
confidence: 93%
“…17 The TPA has been incriminated as a risk factor for cranial cruciate ligament disease based on evidence that a higher TPA was associated with increased cranial cruciate ligament strain. 18 Several studies have found that dogs affected with cranial cruciate ligament disease tend to have a higher TPA than unaffected dogs. 4,19 The mean TPA (28.6 degrees) of dogs predisposed to cranial cruciate ligament disease 4 was similar to the mean TPA of dogs in the >25 degrees group in this trial.…”
Section: Discussionmentioning
confidence: 99%